2020
DOI: 10.1177/1084822320980415
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the COVID-19 Pandemic on Home Health and Home Care Agency Managers, Clients, and Aides: A Cross-Sectional Survey, March to June, 2020

Abstract: Home health and home care (HH&HC) agencies provide essential medical and supportive services to elders and people with disabilities, enabling them to live at home. Home-based care is an important alternative to facility-based care, especially for infection prevention during the COVID-19 pandemic. The majority of the HH&HC workforce is comprised of aides, who also are vulnerable to COVID-19. There are limited data on the COVID-19 experience of HH&HC agencies, clients and aides. A survey of Massachus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 8 publications
6
59
2
Order By: Relevance
“…In addition to these difficulties, other factors participated in a decline of visits by care providers to patients at home, especially during the first wave of the pandemic. Similar to findings observed in the United States [6] , the main reasons behind this reduction are the concerns from families or care providers about bringing or getting Covid-19 in the home, home aides needing to care for their own children due to school closures, or providers being forced to remain in quarantine because they were diagnosed positive to Covid-19. The reduction of home care services has imposed a substantial additional burden on informal caregivers.…”
supporting
confidence: 65%
“…In addition to these difficulties, other factors participated in a decline of visits by care providers to patients at home, especially during the first wave of the pandemic. Similar to findings observed in the United States [6] , the main reasons behind this reduction are the concerns from families or care providers about bringing or getting Covid-19 in the home, home aides needing to care for their own children due to school closures, or providers being forced to remain in quarantine because they were diagnosed positive to Covid-19. The reduction of home care services has imposed a substantial additional burden on informal caregivers.…”
supporting
confidence: 65%
“…During the pandemic, HHC agency leaders, similar to other health care leaders, were confronted with staffing and resource shortages to meet agency needs. 12 Thus, Spanish-speaking HHAs may have been assigned to non-Spanish-speaking patients to ensure adequate patient coverage, exacerbating the need for interpreter services. HHAs in our study highlighted the need for enhanced access to medical interpreters as important to the provision of high-quality care.…”
Section: Discussionmentioning
confidence: 99%
“…11 This demographic profile represents a key segment of the HHC workforce which already experiences high levels of marginalization, and faced greater risk for COVID-19 given the disproportionate impact of the pandemic on Black and Hispanic communities. 12 , 13 , 14 Developing strategies to better support this diverse direct care workforce is critical to meeting the needs of an increasingly diverse aging population in the United States. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…The HC industry applied important lessons from earlier influenza outbreaks and a wide range of recommendations by key stakeholders were brought forward to inform pandemic preparedness planning in HHC and HC [9,10]. Yet, these sectors were still overlooked nationwide at the beginning of the COVID-19 pandemic [5,[11][12][13][14] while challenged to function above capacity to provide home service visits [15].…”
Section: Introductionmentioning
confidence: 99%
“…In summer 2020, the Project team conducted a survey of managers in Massachusetts HC agencies (n = 94) to assess the impacts of COVID-19 on agencies, clients, and aides early in the pandemic. Most agencies (60%) provided services to clients with COVID-19 and three quarters of agencies reported that they employed HC aides who had tested positive for the virus, had been symptomatic, and/or quarantined [14,20].…”
Section: Introductionmentioning
confidence: 99%